Regulatory T cell adoptive transfer alters uterine immune populations, increasing a novel MHC-IIlow macrophage associated with healthy pregnancy - Lewis, Emma L.; Reichenberger, Erin R.; Anton, Lauren; Gonzalez, Michael V.; Taylor, Deanne M.; Porrett, Paige M.; Elovitz, Michal A. (Frontiers in Immunology, 2023)
Intrauterine fetal demise (IUFD) – fetal loss after 20 weeks – affects 6 pregnancies per 1,000 live births in the United States, and the majority are of unknown etiology. Maternal systemic regulatory T cell (Treg) deficits have been implicated in fetal loss, but whether mucosal immune cells at the maternal-fetal interface contribute to fetal loss is under-explored. We hypothesized that the immune cell composition and function of the uterine mucosa would contribute to the pathogenesis of IUFD. To investigate local immune mechanisms of IUFD, we used the CBA mouse strain, which naturally has mid-late gestation fetal loss. We performed a Treg adoptive transfer and interrogated both pregnancy outcomes and the impact of systemic maternal Tregs on mucosal immune populations at the maternal-fetal interface. Treg transfer prevented fetal loss and increased an MHC-IIlow population of uterine macrophages. Single-cell RNA-sequencing was utilized to precisely evaluate the impact of systemic Tregs on uterine myeloid populations. A population of C1q+, Trem2+, MHC-IIlow uterine macrophages were increased in Treg-recipient mice. The transcriptional signature of this novel uterine macrophage subtype is enriched in multiple studies of human healthy decidual macrophages, suggesting a conserved role for these macrophages in preventing fetal loss.